Postoperative (Chemo)Radiotherapy for Oral Cavity Squamous Cell Carcinomas: Outcomes and Patterns of Failure. Issue 1 (January 2017) - Metcalfe, E.; Aspin, L.; Speight, R.; Ermiş, E.; Ramasamy, S.; Cardale, K.; Dyker, K.E.; Sen, M.; Prestwich, R.J.D.
Abstract: Aims: To determine outcomes after adjuvant radiotherapy for squamous cell carcinoma of the oral cavity and to correlate locoregional recurrence patterns with radiotherapy target volumes. Materials and methods: All patients receiving adjuvant radiotherapy ± chemotherapy after surgery with curative intent for oral cavity squamous cell carcinoma between 2007 and 2012 were retrospectively analysed. Locoregional recurrences were reconstructed on the planning computed tomography scan by both deformable image co-registration and by visual assessment. Recurrences were categorised as in-field, marginal or out-of-field if >95%, 20–95%, and <20% of the recurrence volume was encompassed by 95% of the prescription isodose, respectively. Results: In total, 106 patients with a median follow-up of 42 months were included. Oral cavity subsites included oral tongue (54%) and floor of mouth (32%). Thirty (28%) patients received concurrent chemotherapy. Fifty-five (52%) patients received bilateral neck radiotherapy. Two year overall, disease-free, local disease-free, regional disease-free and distant metastases-free survival were 72, 83, 92, 89, 94%, respectively. On multivariate analysis, extracapsular nodal spread was the only factor significantly associated with inferior overall survival. Fourteen (13%) patients have experienced locoregional failure. Of the eight local recurrences at the primary tumour site, four, three and one were classified as in-field, marginal and out-of-field, respectively. Of 10 regional recurrences, one, one and eight were in-field, marginal and out-of-field. There were 7/21 (33%) contralateral regional recurrences in patients with pN2a/b disease who did not receive contralateral neck irradiation; there were 0/21 (0%) and 0/9 (0%) contralateral regional recurrences in patients with pN0 or pN1 disease, respectively, who did not receive contralateral neck irradiation. Conclusion: Marginal recurrences highlight the need for generous target volume delineation. Based upon rates of contralateral regional recurrences, a comprehensive approach to target volume selection should be advised for tumour subsites with bilateral lymphatic drainage in the presence of pN2a/b disease. Highlights: Achieving locoregional control remains a challenge for oral cavity cancer. Aim was to examine patterns of disease recurrence after adjuvant radiotherapy. Marginal recurrences highlight the need for generous target volume delineation. Contralateral neck irradiation should be considered with pN2a/b disease.